How to Solve Accounting Problems–Intermediate and Advanced (Book). - Nielsen, Gordon L. (The Accounting Review, 1962)
Reviews the book "How to Solve Accounting Problems-Intermediate and Advanced," by W. Rogers Hammond and Houston D. Smith.